Living Standards in Southeast Asia : Changes over the Long Twentieth Century, 1900-2015 - Booth, Anne, 1946- (Transforming Asia., 2020)
Living Standards in Southeast Asia: Changes over the Long Twentieth Century, 1900-2015 examines changes in living standards across the ten countries of Southeast Asia (Indonesia, Malaysia, Singapore, Philippines, Thailand, Brunei, Myanmar, Vietnam, Cambodia and Laos) from the early years of the 20th century to the early 21st century. It covers both the last decades of the colonial period, the transition to independence and the decades from 1960 to the 2010s. The study uses a range of monetary and non-monetary indicators to assess how living standards have changed over time. It examines the outcomes in the context of debates about economic growth, inequality and poverty alleviation which began in the 1960s and 1970s, and continue to the present.